Analisis Time Cost Trade Off Untuk Mengejar Keterlambatan Pelaksanaan Proyek Di Bandar Lampung - Ika Kustiani; Amrif Ma'ruf Siregar; Anastasia Florensia Mela (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2016)
During the execution of construction projects, often there is a mismatch between the planned schedule and realization. It could lead to the overruns of the implementation time and cost. De - lays can be overcomed by acceleration of the implementation in order to achieve the targeted plan. However, in the decision to speed up the implementation of the work, it is necessary to take into account the expected results of financing so that the minimum cost achieve without neglecting the required standards of quality. The alternatives that can be used are the addition of works and the labors themselves. From the analysis results obtained that the acceleration that produces the minimum total cost (not including indirect costs) for the project Lampung Hotel Zodiac is to use more labor, the total cost and the total duration of each to Rp. 29,523,160,619 be 309 days. Acceleration to Hotel Park In By Radisson is to accelerate without penalty using more labor, the total cost and the total duration of each to Rp. 201 974 119 946 and 196 days. While Toko Mitra Hasil Sentosa project is to in - crease working hours, with the total cost and the total duration of each to Rp. 18,348,782,435 and 263 days.